Significant Increase in Nutrient Stocks Following Phragmites australis Invasion of Freshwater Meadow Marsh but Not of Cattail Marsh - Yuckin, Sarah; Rooney, Rebecca (Frontiers in Environmental Science, 2019)
Invasive species are a threat to biodiversity and can cause ecological degradation, however, well-established invasive species may serve valuable ecological functions. For example, in the Laurentian Great Lakes, where nutrient pollution is a major issue, highly productive Phragmites australis (European Common Reed) may provide a nutrient retention service. Yet there is a lack of research comparing carbon and macronutrient stocks in P. australis with resident plant communities, such as cattail and meadow marsh. We quantified the effect of P. australis invasion on carbon and macronutrient standing stocks in a freshwater coastal marsh by comparing the above- and belowground biomass, tissue nutrient concentrations, and annual nutrient standing stocks in marsh invaded by P. australis with cattail marsh (dominated by Typha spp.) and meadow marsh (dominated by Calamagrostis canadensis), which are being displaced by P. australis in Lake Erie coastal marsh. We conclude that the effect of P. australis invasion on carbon and macronutrient standing stocks is dependent on the plant community being replaced. The annual standing stock of carbon, nitrogen, phosphorus, and potassium are consistent between cattail marsh and P. australis-invaded marsh, though cattail marsh contains more magnesium (112 % mean increase) and calcium (364 % mean increase). In contrast, when P. australis replaces meadow marsh, the standing stocks of all measured nutrients and carbon increase significantly (103 - 188 % mean increase). Our study highlights that plant invasions may create trade-offs between ecosystem services. In our case, the increase in nutrient standing stocks when P. australis invades meadow marsh should be weighed against the documented reductions in biodiversity and habitat value.